Mucoromycotina Fungi Possess the Ability to Utilize Plant Sucrose as a Carbon Source: Evidence From Gongronella sp. w5 - Wang, Xiaojie; Fang, Junnan; Liu, Pu; Liu, Juanjuan; Fang, Wei; Fang, Zemin; Xiao, Yazhong (Frontiers in Microbiology, 2021)
Mucoromycotina is one of the earliest fungi to establish a mutualistic relationship with plants in the ancient land. However, the detailed information on their carbon supply from the host plants is largely unknown. In this research, a free-living Mucoromycotina called Gongronella sp. w5 (w5) was employed to explore its effect on Medicago truncatula growth and carbon source utilization from its host plant during the interaction process. W5 promoted M. truncatula growth and caused the sucrose accumulation in M. truncatula root tissue at 16 day-post-inoculation (dpi). The transportation of photosynthetic product sucrose to the rhizosphere by M. truncatula root cells seemed accelerated by upregulating the SWEET gene. A predicted cytoplasmic invertase (GspInv) gene and a sucrose transporter (GspSUT1) homology gene in the w5 genome upregulated significantly at the transcriptional level during w5–M. truncatula interaction at 16 dpi, indicating the possibility of utilizing plant sucrose directly by w5 as the carbon source. Further investigation showed that the purified GspInv displayed an optimal pH of 5.0 and a specific activity of 3380 ± 26 U/mg toward sucrose. The heterologous expression of GspInv and GspSUT1 in Saccharomyces cerevisiae confirmed the function of GspInv as invertase and GspSUT1 as sugar transporter with high affinity to sucrose in vivo. Phylogenetic tree analysis showed that the ability of Mucoromycotina to utilize sucrose from its host plant underwent a process of “loss and gain”. These results demonstrated the capacity of Mucoromycotina to interact with extant land higher plants and may employ a novel strategy of directly up-taking and assimilating sucrose from the host plant during the interaction.